Smerte kræver øvelse. En undersøgelse af smerte, body suspension og førstehed - Mortensen, Maria (Kvinder, Køn & Forskning, 2018)
Pain takes practice. A study of pain, body suspension and Firstness. This study examines the Firstness of pain as an understanding of pain as isolating and destructive, as well as entering the debate about the lack of intentionality of pain. In the article I draw on two empirical examples from fieldwork conducted at body suspension events in Copenhagen in 2014/2015. Throughout the article I apply a theoretical framework from the field of affect theory and new materialisms, in the form of Sara Ahmed and Robin Bauer. The analyses of the empirical examples show how pain can work as a way of diverting attentiveness from the bodies surrounding the body in pain, as well as creating transgressive bodies, which exceeds the singular body in pain. I hereby argue that the object of pain should not be limited to the singular body. Instead we must understand the object of pain, as well as the body in pain, as multiple and situational. Pain works both inside bodies, outside bodies and between bodies.